A morphological novelty for feeding and sound production in the yellowtail clownfish. Issue 4 (16th March 2015) - Olivier, Damien; Frédérich, Bruno; Herrel, Anthony; Parmentier, Eric
ABSTRACT: The yellowtail clownfish Amphiprion clarkii is able to close its mouth very quickly by means of the cerato‐mandibular (c‐md) ligament, a synapomorphic trait of Pomacentridae joining the hyoid bar to the medial part of the lower jaw. This fast closure induces tooth collision, thus producing sounds that the clownfish uses during agonistic behaviors. To investigate whether this rapid jaw movement is also used during feeding, we analyzed the kinematics of sound production and feeding. Sound production, feeding on live planktonic prey, and feeding on food attached to tweezers was filmed with a high‐speed camera. Three kinds of kinematic patterns were detected and were associated with the two different types of food presented: one performed to catch planktonic prey ( PP ), and two (called B‐1 and B‐2 ) to bite attached food items. The kinematic pattern of B‐2 is similar to that observed during sound production ( SP ) and the transection of the c‐md ligament highlights that sound production and biting‐2 motions are dependent on this morphological trait. Our data show that the c‐md ligament in addition to its role in sound production allows duplication of the mouth‐closing mechanism during feeding. This highlights the key role played by the c‐md ligament in sound production and feeding on attached prey. J. Exp. Zool. 323A: 227–238, 2015 . © 2015 Wiley Periodicals, Inc.